THE INFLUENCE OF HYDROUS MN-ZN OXIDES ON DIEL CYCLING OF ZN IN AN ALKALINE STREAM DRAINING ABANDONED MINE LANDS - Shope C.L.; Xie Y.; Gammons C.H. (My University, 2006)
Many mining-impacted streams in western Montana with pH near or above neutrality display large (up to 500%) diel cycles in dissolved Zn concentrations. The streams in question typically contain boulders coated with a thin biofilm, as well as black mineral crusts composed of hydrous Mn-Zn oxides. Laboratory mesocosm experiments simulating diel behavior in High Ore Creek (one of the Montana streams with particularly high Zn concentrations) show that the Zn cycles are not caused by 24-h changes in streamflow or hyporheic exchange, but rather to reversible in-stream processes that are driven by the solar cycle and its attendant influence on pH and water temperature (T). Laboratory experiments using natural Mn-Zn precipitates from the creek show that the mobilities of Zn and Mn increase nearly an order of magnitude for each unit decrease in pH, and decrease 2.4-fold for an increase in T from 5 to 20°C. The response of dissolved metal concentration to small changes in either pH or T was rapid and reversible, and dissolved Zn concentrations were roughly an order of magnitude higher than Mn. These observations are best explained by sorption of Zn2+ and Mn2+ onto the secondary Mn-Zn oxide surfaces. From the T-dependence of residual metal concentrations in solution, approximate adsorption enthalpies of +50 kJ/mol (Zn) and +46 kJ/mol (Mn) were obtained, which are within the range of enthalpy values reported in the literature for sorption of divalent metal cations onto hydrous metal oxides. Using the derived pH- and T-dependencies from the experiments, good agreement is shown between predicted and observed diel Zn cycles for several historical data sets collected from High Ore Creek. © 2006 Elsevier Ltd. All rights reserved.